Causal relationships among the gut microbiome, short-chain fatty acids and metabolic diseases - Sanna, Serena; van Zuydam, Natalie R.; Mahajan, Anubha; Kurilshikov, Alexander; Vich Vila, Arnau; Võsa, Urmo; Mujagic, Zlatan; Masclee, Ad A. M.; Jonkers, Daisy M. A. E.; Oosting, Marije; Joosten, Leo A. B.; Netea, Mihai G.; et al. (Nature genetics, 2019)
Microbiome-wide association studies on large population cohorts have highlighted associations between the gut microbiome and complex traits, including type 2 diabetes (T2D) and obesity 1 . However, the causal relationships remain largely unresolved. We leveraged information from 952 normoglycemic individuals for whom genome-wide genotyping, gut metagenomic sequence and fecal short-chain fatty acid (SCFA) levels were available 2 , then combined this information with genome-wide-association summary statistics for 17 metabolic and anthropometric traits. Using bidirectional Mendelian randomization (MR) analyses to assess causality 3 , we found that the host-genetic-driven increase in gut production of the SCFA butyrate was associated with improved insulin response after an oral glucose-tolerance test ( P = 9.8 × 10 −5 ), whereas abnormalities in the production or absorption of another SCFA, propionate, were causally related to an increased risk of T2D ( P = 0.004). These data provide evidence of a causal effect of the gut microbiome on metabolic traits and support the use of MR as a means to elucidate causal relationships from microbiome-wide association findings. Mendelian randomization analyses using genotyping data, gut metagenomic sequence and fecal short-chain-fatty-acid levels from 952 individuals combined with GWAS data show evidence of a causal effect of the gut microbiome on metabolic traits.